2014
DOI: 10.1002/polb.23497
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity, impedance, and percolation behavior of carbon nanofiber and carbon nanotube containing gellan gum hydrogels

Abstract: The electrical impedance behavior of gellan gum (GG), GG-carbon nanotube, and GG-carbon nanofiber hydrogel composites is reported. It is demonstrated that the impedance behavior of these gels can be modeled using a Warburg element in series with a resistor. Sonolysis (required to disperse the carbon fillers) does not affect GG hydrogel electrical conductivity (1.2 6 0.1 mS/cm), but has a detrimental effect on the gel's mechanical characteristics. It was found that the electrical conductivity (evaluated using i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…Apart from this, GG has been utilized in biomedicine [59][60][61][62][63], and nanotechnology [64,65] and composites [66][67][68][69][70][71][72] in the material science field by taking advantage of its peculiar gelation and rheological properties [73,74]. For example, GG composites containing carbon nanotube [66][67][68][69][70][71] or graphene [72] as fillers were also reported to exhibit good conductivity. Recently, we found that GG can efficiently reduce GO and adsorb onto the reduced GO nanosheets giving a stable GGreduced GO aqueous dispersion [75].…”
Section: Introductionmentioning
confidence: 98%
“…Apart from this, GG has been utilized in biomedicine [59][60][61][62][63], and nanotechnology [64,65] and composites [66][67][68][69][70][71][72] in the material science field by taking advantage of its peculiar gelation and rheological properties [73,74]. For example, GG composites containing carbon nanotube [66][67][68][69][70][71] or graphene [72] as fillers were also reported to exhibit good conductivity. Recently, we found that GG can efficiently reduce GO and adsorb onto the reduced GO nanosheets giving a stable GGreduced GO aqueous dispersion [75].…”
Section: Introductionmentioning
confidence: 98%
“…However, owing to the weak and brittle nature of common synthetic hydrogels, existing hydrogel electronics and devices mostly suffer from the limitation of low mechanical robustness and low stretchability. On the other hand, while hydrogels with extraordinary mechanical properties, or so-called tough hydrogels, have been recently developed [1822] , it is still challenging to fabricate tough hydrogels into stretchable electronics and devices capable of novel functions. The design of robust, stretchable and biocompatible hydrogel electronics and devices represents a critical challenge in the emerging field of soft materials, electronics and devices.…”
mentioning
confidence: 99%
“…The lower frequency range includes a second possible time constant forming, which would be attributed to the tattoo electrode‐hydrogel interface. It is possible that other contributions, such as, polarization of the electrode‐hydrogel interface or diffusional properties were present in the lower frequency region . In this study, the bulk hydrogel matrix comprising of the polymer network interacting with both free and bound water in the higher frequency range was the region of interest.…”
Section: Resultsmentioning
confidence: 99%